Self-Driven Service Learning: Community-Student-Faculty Collaboratives Outside of the Classroom - Verónica A. Segarra (American Society for Microbiology, 2015)
Service learning is a community engagement pedagogy often used in the context of the undergraduate classroom to synergize course-learning objectives with community needs. We find that an effective way to catalyze student engagement in service learning is for student participation to occur outside the context of a graded course, driven by students’ own interests and initiative. In this paper, we describe the creation and implementation of a self-driven service learning program and discuss its benefits from the community, student, and faculty points of view. This experience allows students to explore careers in the sciences as well as identify skill strengths and weaknesses in an environment where mentoring is available but where student initiative and self-motivation are the driving forces behind the project’s success. Self-driven service learning introduces young scientists to the idea that their careers serve a larger community that benefits not only from their discoveries but also from effective communication about how these discoveries are relevant to everyday life.